Treatment of juvenile hallux valgus interphalangeus with a double compression headless bone screw - Göksel, Ferdi (BMJ Case Rep, 2015)
A 14-year-old girl presented with idiopathic valgus deformity of her left great toe at the interphalangeal joint (IPJ). The deformity, which had been present but asymptomatic for the past 4 years, began to enlarge and cause discomfort. The measured IPJ angle on anteroposterior standing X-ray was 26°. We treated the toe by medial closing wedge osteotomy and fixation with a double compression headless bone screw (DCHBS). Postoperative hallux valgus interphalangeus (HVI) angle was 14°.